Effects of different rootstocks on physical traits of Siirt and Ohadi pistachio cultivars - Turker S.; Ak B.E. (XIV GREMPA Meeting on Pistachios and Almonds, 2010)
Rootstocks are a very important part of pistachio cultivars because of their different effects on yield. There are different purposes for the use of rootstocks. Generally, they are used for diseases and pests control, besides of getting good quality and more yield, and for the uptake more nutrients from the soil. Because of the different vigor levels of the rootstocks, they have influence on the growth and development of the scions. In this experiment, the effects of three different pistachio rootstocks (P. vera, P. khinjuk and P. atlantica) on shell dehiscence, filling and empty fruits of two different cultivars (Siirt and Ohadi) were investigated. According to the results, rootstocks were effective on shell dehiscence and empty fruit and total filled nuts. The effectiveness of rootstocks was different depending on the traits.
14. GREMPA Meeting on Pistachios and Almonds, 2008/03/30-2008/04/04, Athens (Greece)